2013
DOI: 10.1039/c3ra42617c
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles anchored reduced graphene oxide as catalyst for oxygen electrode of rechargeable Li–O2 cells

Abstract: Gold nanoparticles decorated reduced graphene oxide (Au-RGO) catalyst for O 2 electrode is prepared by in situ reduction of Au 3+ ions and graphene oxide dispersed in water. The Au nanoparticles are uniformly distributed on the two-dimensional RGO layers. Li-O 2 cells assembled in a non-aqueous electrolyte using Au-RGO catalyst exhibit an initial discharge capacity as high as 5.89 mA h cm À2 (5230 mA h g À1 ) at a current density of 0.1 mA cm À2 . The voltage gap between the charge and discharge curves is less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 48 publications
(59 reference statements)
0
25
0
Order By: Relevance
“…[19][20][21] The glass mat was soaked in an electrolyte containing 1.0 M LiPF 6 in DMSO before being inserted into the cell. The suspension (200 ml) was transferred onto a glassy carbon (GC) disk electrode with an area of 0.0314 cm 2 (diameter = 3 mm) and the solvent was evaporated in air.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] The glass mat was soaked in an electrolyte containing 1.0 M LiPF 6 in DMSO before being inserted into the cell. The suspension (200 ml) was transferred onto a glassy carbon (GC) disk electrode with an area of 0.0314 cm 2 (diameter = 3 mm) and the solvent was evaporated in air.…”
Section: Methodsmentioning
confidence: 99%
“…20 This side was exposed to O 2 gas. In the present study, 1.0 M LiPF 6 dissolved in DMSO was used as the electrolyte and porous Toray carbon paper was used as the current-collecting substrate.…”
Section: Li-o 2 Cell Studiesmentioning
confidence: 99%
“…Moreover, the energy efficiency (output energy/ input energy) is unacceptably low for use as an energy storage system. [11,12]…”
mentioning
confidence: 99%
“…Moreover, the energy efficiency (output energy/ input energy) is unacceptably low for use as an energy storage system. [11,12] To overcome the limitations of current Li-O 2 battery technology, diverse approaches combining multiple strategies are required. One of the important elemental technologies related to this involves the promotion of the catalytic activity during the charging reaction of Li 2 O 2 , which is critical to decrease the polarization and increase the reversibility.…”
mentioning
confidence: 99%
“…Therefore, the recent studies about LABs have been directed to design and develop electrocatalysts for the air cathode. For instance, Munichandraiah et al reported an initial discharge capacity of 5230 mA h g À1 at a rate of 90 mA g À1 and a cycle life of 120 cycles in the presence of rGO supported Au nanoparticles (NPs) under the atmosphere of dry-oxygen gas [14]. In this regard, rGO supported Pd catalyst either in monometallic or bimetallic alloy structure in the presence of a nonprecious metal might also be considered for the development of more economical cathode catalysts for the LABs because Pd is less expensive than Au and provide higher capacity compared to other precious metals such as Pt ans Ru at the air cathode [15].…”
Section: Introductionmentioning
confidence: 99%